2021
DOI: 10.1186/s13054-021-03493-w
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and microbiology of ventilator-associated pneumonia in COVID-19 patients: a multicenter retrospective study in 188 patients in an un-inundated French region

Abstract: Background The COVID-19 pandemic is responsible for many hospitalizations in intensive care units (ICU), with widespread use of invasive mechanical ventilation (IMV) which exposes patients to the risk of ventilator-associated pneumonia (VAP). The characteristics of VAP in COVID-19 patients remain unclear. Methods We retrospectively collected data on all patients hospitalized for COVID-19 during the first phase of the epidemic in one of the seven IC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
95
2
10

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 99 publications
(119 citation statements)
references
References 29 publications
12
95
2
10
Order By: Relevance
“…Cumulative estimates of occurrence of VAP sorted by the sample size of the included studies are provided as Figure S1 in Supplementary Material S2. Eleven of the included studies reported data on mortality in patients with COVID-19 and VAP [9,15,16,20,21,[23][24][25][30][31][32]. The pooled estimated occurrence of mortality (at the longest available follow-up) was 42.7% (95% C.I.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Cumulative estimates of occurrence of VAP sorted by the sample size of the included studies are provided as Figure S1 in Supplementary Material S2. Eleven of the included studies reported data on mortality in patients with COVID-19 and VAP [9,15,16,20,21,[23][24][25][30][31][32]. The pooled estimated occurrence of mortality (at the longest available follow-up) was 42.7% (95% C.I.…”
Section: Discussionmentioning
confidence: 99%
“…The full search output is available as Supplementary Material S3. After the exclusion of duplicates and not relevant records, twenty studies were included in the systematic review and metaanalysis, for a total of 2611 patients with COVID-19 who developed at least one episode of VAP [9,[15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33]. The process of inclusion and exclusion is detailed in the PRISMA flow diagram, provided in Figure 1.…”
Section: Characteristics Of Included Studies and Patientsmentioning
confidence: 99%
See 3 more Smart Citations